CRISPR-Mediated Single Nucleotide Polymorphism Modeling in Rats Reveals Insight Into Reduced Cardiovascular Risk Associated With Mediterranean G6PD Variant. Issue 2 (August 2020) - Kitagawa, Atsushi; Kizub, Igor; Jacob, Christina; Michael, Kevin; D'Alessandro, Angelo; Reisz, Julie A.; Grzybowski, Michael; Geurts, Aron M.; Rocic, Petra; Gupte, Rakhee; Miano, Joseph M.; Gupte, Sachin A.
Abstract : Epidemiological studies suggest that individuals in the Mediterranean region with a loss-of-function, nonsynonymous single nucleotide polymorphism (S188F), in glucose-6-phosphate dehydrogenase ( G6pd ) are less susceptible to vascular diseases. However, this association has not yet been experimentally proven. Here, we set out to determine whether the Mediterranean mutation confers protection from vascular diseases and to discover the underlying protective mechanism. We generated a rat model with the Mediterranean single nucleotide polymorphism (G6PD S188F ) using CRISPR-Cas9 genome editing. In rats carrying the mutation, G6PD activity, but not expression, was reduced to 20% of wild-type (WT) littermates. Additionally, unbiased metabolomics analysis revealed that the pentose phosphate pathway and other ancillary metabolic pathways connected to the pentose phosphate pathway were reduced ( P <0.05) in the arteries of G6PD S188F versus WT rats. Intriguingly, G6PD S188F mutants, as compared with WT rats, developed less large arterial stiffness and hypertension evoked by high-fat diet and nitric oxide synthase inhibition with L-N G -nitroarginine methyl ester. Intravenous injection of a voltage-gated L-type Ca 2+ channel agonist (methyl 2, 6-dimethyl-5-nitro-4-[2-(trifluoromethyl)phenyl]-1, 4-dihydropyridine-3-carboxylate; Bay K8644) acutely increased blood pressure in WT but not in G6PD S188F rats. Finally, our results suggested that (1) lower resting membrane potential of smooth muscle caused by increased expression of K + channel proteins and (2) decreased voltage-gated Ca 2+ channel activity in smooth muscle contributed to reduced hypertension and arterial stiffness evoked by L-N G -nitroarginine methyl ester and high-fat diet to G6PD S188F mutants as compared with WT rats. In summary, a mutation resulting in the replacement of a single amino acid (S188F) in G6PD, the rate-limiting enzyme in the pentose phosphate pathway, ascribed properties to the vascular smooth muscle that shields the organism from risk factors associated with vascular diseases. Abstract : Supplemental Digital Content is available in the text.